The Effect of Fibre Direction on the Mechanical Properties of Polyester Matrix-Based Palm Oil Fibre Composite - Yulianto, Dody; Arman Maulana; Shandy Kurniadi; Ari Prasetyo; Sehat Abdi Saragih; Jhonni Rahman; Kurnia Hastuti; Eddy Elfiano (UIR PRESS, 2026)
The increasing use of composite materials, especially for the two-wheeled vehicle industry, requires an in-depth study of fibre direction. Where the fiber direction can determine the occurrence of initial damage to the composite material. This study aims to produce a composite board from oil palm fruit fibre reinforced with a polyester matrix. In this study, the composite board consists of 3 types, namely sample 1 (discontinuous direction 0°), sample 2 (discontinuous direction 90°), and sample 3 (random fibre direction). The highest bending and impact test results were in specimen 1 with a 0° fibre direction, namely 63.93 MPa and 0.519 Joules/mm2, while the lowest bending and impact test results were in specimen 3 with a random fibre direction, namely 58.63 MPa and 0.382 Joules/mm2. Specimens with horizontal fibre directions have higher strength values. When the fibres are arranged in a 90° direction and a random direction, the mechanical strength is lower, because the load is mostly borne by the material matrix, which is generally weaker than the fibres. Macrophotography at 0° shows that the bonding mechanism of oil palm fruit fibres with the polyester resin matrix is quite good, with visible fibre pullout. This indicates that the bond between the fibre and the matrix weakens as the applied load increases. When the matrix fails, the fibres can still bear the load, so the fracture process does not occur simultaneously with the matrix failure. If the composite fibres become more brittle and the load is distributed to the fibres, which pulls them out, this will result in high toughness and bending strength.